Influência da “ceva” na fauna endoparasitária de Brycon falcatus (Characidae: Bryconinae) do rio Teles Pires, sul da Amazônia. - Boller, Larissa Liber de Almeida (2023)
Studies on endoparasitic fauna provide valuable biological information, such as migration habits, population breakdown and host feeding habits. Several species of endoparasites are transmitted via trophic web and have complex life cycles with two or more hosts, which characterizes the trophic interactions between organisms. In this sense, the objective of this work was to evaluate the impact of attractant feeds (soybeans, corn) on the diet and on the endoparasitic fauna of Brycon falcatus, collected in the Amazon basin. The specimens were collected using a line hook, fishing rod and gill nets. Then the fish were euthanized and the stomach and intestines of each specimen were analyzed fresh. Two species of nematodes were identified, Procamallanus (Spirocamallanus) inopinatus and Philonema sp.. The diet of B. falcatus was composed of aquatic and terrestrial insects and attractant feeds, which are composed of soybeans and corn, being considered as an item of anthropic origin, which characterized it as an omnivore with a tendency to herbivory. The aquatic insects found in the diet of B. falcatus may possibly act as intermediate hosts for P. (S.) inopinatus and Philonema sp.. Among the endoparasites, it was observed that P. (S.) inopinatus presented greater abundance, intensity and prevalence parasitic compared to Philonema sp.. It was found that non-parasitized individuals had a higher condition factor than parasitized individuals. There was a significant difference in the condition factor between individuals who had the presence or absence of attractant feeds in the digestive tract. Consequently, B. falcatus was influenced by anthropic items on Kn, as specimens that did not consume this food item had a higher Kn compared to fish that ate attractant feeds. Based on the results obtained, it is possible to verify that the diet of B. falcatus had a greater representation of natural food items, such as stems and barks, Coleoptera and Ephemeroptera. However, there was an impact of attractant feeds ingestion on the relative condition factor of the specimens, requiring greater inspection to avoid this anthropic action that can negatively affect the environmental and the local fauna.